Understanding the Intentions of Accounting Students to Pursue Career as a Professional Accountant - Kiky Srirejeki; Saras Supeno; Agus Faturahman (Bina Nusantara University, 2019)
The aim of this research was to investigate the contributing factors that influenced the intentions of accounting students in Indonesia to pursue a career as a professional accountant. The researchers applied a quantitative method to present a descriptive analysis of accounting students perception. The researchers collected 439 questionnaires from accounting students across universities in Indonesia with simple random sampling technique. The findings show that the intrinsic factor (attitude) and parental or peers influence (subjective norm) affect the students’ intention to pursue a career as a professional accountant. The results of this research are expected to give insights to university’s accounting department and professional bodies such as Institute of Indonesia Chartered Accountant and Institute of Certified Public Accountant to formulate strategies to achieve the desired number of accountants in Indonesia. In addition, regulatory agencies can use these findings as a basis to develop policies that guide universities or professional bodies to make the accounting profession more desirable.